A genetically confirmed hybrid between Natrix astreptophora and N. maura, two deeply divergent and ancient snake species - Andrea Criado-Flórez; Juan Pablo González de la Vega; Gabriel Martínez del Marmol; Uwe Fritz (Herpetozoa)
Using two mitochondrial DNA fragments and six nuclear genes, we confirmed that a morphologically intermediate snake, captured in Andalusia, southwestern Spain (municipality of Huelva), was an F1 hybrid between a female Natrix astreptophora and a male N. maura. The two parental species diverged 21.5 million years ago, which is why their capability to hybridize is remarkable. The interspecific mating could have been facilitated by the rarity of N. astreptophora and the abundance of N. maura in southwestern Spain, making it difficult for N. astreptophora females to find conspecific males. In the face of previously published genomic signatures for ancient gene flow between N. astreptophora and N. maura, our finding raises the question of whether occasional hybridization still contributes to a continued exchange of genetic information between these two deeply divergent and old taxa.